2016
DOI: 10.1016/j.ijhydene.2015.11.093
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive mesh refinement based simulations of three-dimensional detonation combustion in supersonic combustible mixtures with a detailed reaction model

Abstract: Although the overdrive degree of the 3D detonation is smaller than that of the 2D case, more complex and irregular detonation fronts can be observed in the 3D case compared with the 2D detonation, which is likely because of the propagation of transverse waves and collisions of triple lines in multi-directions in 3D detonations. After the hot jet is shut down, the newly formed 2D Chapman-Jouguet (CJ) detonation has almost the same characteristic parameters with the corresponding 3D case, indicating that the 2D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…The formation of an overdriven detonation is a result of the continuous hot jet injection [27]. Because of the combination of two different mixtures in the channel, the detonation front in Fig.15 varies considerably, which is different from that in uniform supersonic combustible mixtures [65]. However, according to Fig.16(a), oscillations of the detonation front are very regular with an oscillation period of 21.72 μs…”
Section: Mixture Group G21mentioning
confidence: 97%
“…The formation of an overdriven detonation is a result of the continuous hot jet injection [27]. Because of the combination of two different mixtures in the channel, the detonation front in Fig.15 varies considerably, which is different from that in uniform supersonic combustible mixtures [65]. However, according to Fig.16(a), oscillations of the detonation front are very regular with an oscillation period of 21.72 μs…”
Section: Mixture Group G21mentioning
confidence: 97%
“…6(a). It has been demonstrated that the Mach stem is in fact a local Mach detonation (Cai et al 2016c), indicating the detonation onset in the supersonic combustible mixture. Due to the formation of the contractive passage generated by the upper wall and the free boundary of the slip line directly behind the triple point, the Mach detonation propagates forward towards the incoming combustible mixture, as shown in Fig.…”
Section: Hot Jet Initiationmentioning
confidence: 99%
“…Ref [21][22][23] ). Cai et al 24 found that the sidewalls in a three-dimensional rectangular channel can help realize detonation initiation in supersonic combustible mixtures. However, few studies have focused on detonation initiation in a circular tube, which is more general in practical applications.…”
Section: Introductionmentioning
confidence: 99%